(untitled) (Biological Sciences - PJSIR, 2005)
Rice bran lipase-1 (lip-1) was treated with various groups of specific amino acids modifying reagents. Modifica- tion of arginine and histidine residues did not affect the lipolytic activities of the lipases. Acetylation of the lipases with acetic anhydride led to a complete loss of their lipolytic properties. However, citraconylation did not affect the lipolytic properties indicating the involvement of tyrosine residues at or near the active site of lipases. Acetylation of tyrosyl groups with N-acetylimidazole strongly reduced the lipolytic activities of lipases and the loss in activities was restored on deacetylation of tyrosyl groups. Modification of serine residues with diisopropyl fluorophosphate (DFP) inactivated the lipases completely, while the lipolytic activities of the lipases were reduced by about 50% after modification of cysteine residues with 5,5´-dithio-bis-2-nitrobenzoic acid (DTNB). Oxidation of lip-1 by N-bromosuccinimide (NBS) destroyed its activity completely, indicating the involvement of tryptophan residues at the active site. It is suggested from the results presented in this study that tyrosine, tryptophan and serine residues are located at or near the active site of lip-1.